Comparing the anthropometrics, body composition, and strength performance of male and female Italian breaking athletes: A pilot study - Ruscello, B.; Morganti, G.; De Fano, A.; Mancina, F.; Lunetta, L.; Di Mauro, G.; Cogoni, C.; Pagano, E.; Brigati, N. M.; Di Castro, A.; Gianfelici, A.; Spada, R.; et al. (Sports, 2024)
Breaking is a performative art that has recently undergone a process of sportification, developing into an aesthetic sport included in the 2024 Paris Olympic Games. Despite its growing worldwide popularity, there is a lack of research on Breaking. Accordingly, this pilot study`s aim was twofold: (a) to provide an initial understanding of the anthropometric measures, body composition data, somatotype profiles, and strength performance of male (B-boys) and female (B-girls) Italian Breakers divided into elite (international) and sub-elite (national) levels and (b) to guide further research on the area, providing the methodological approach for future investigations. A total of 24 B-boys (elite n = 5; sub-elite n = 19) and 9 B-girls (elite n = 3; sub-elite n = 6) were included in this study. Descriptive analyses revealed that B-boys and B-girls displayed low height and weight (1.70 m (63.8 kg) and 1.58 m (54.2 kg), respectively), low levels of body fat percentages (10.3% and 17.6%, respectively), and a balanced mesomorph somatotype (2.28-4.64-2.69 and 2.34-5.16-2.38, respectively), revealing a marked development of muscular mass. Due to the small sample size, Welch`s test and correlation analyses did not report any elite vs. sub-elite difference. It was hypothesized that Breakers` morphological profiles result from the selection procedures and training regimens related to Breaking aesthetic, athletic, and physiological demands.